Antimicrobial and biocide resistance in Staphylococcus aureus: genomic features, decontamination strategies, and the role of S. aureus complex-related species, with a focus on ready-to-eat food and food-contact surfaces - Chieffi, Daniele; Fanelli, Francesca; Fusco, Vincenzina (Frontiers in Food Science and Technology, 2023)
Staphylococcus aureus can proliferate in a broad range of foods as well as contact surfaces. The ability to grow as a biofilm enhances its survival to cleaning agents and the chance to enter the food chain. This increases the risk for consumer and food workers’ health, since this pathogen has been associated with a wide variety of human infection, bacteremia, pneumonia etc., as well as with food poisoning caused by the production of exotoxins. To worsen this scenario, S. aureus harbors several antibiotic and biocide resistance genes (ARG and BRG), which increase its pathogenicity and reduce the efficacy of antimicrobial treatments. Several methods have been recently investigated for the eradication of S. aureus biofilm in the food processing environments, including the use of natural compounds as well as physical methods and new food-contact materials. In this review we will provide an overview on ARG, BRG and WGS based methods recently implemented for their surveillance. Furthermore, we will also describe novel antimicrobials, natural compounds or new food contact materials recently proposed for eradicating S. aureus biofilms in the food sector. Finally, it will be also discussed if S. aureus complex related species are emerging as new antimicrobial-resistant pathogens of the food chain.